PENERAPAN METODE PEMBELAJARAN PESAWAT MASALAH UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN KOLOID DI KELAS XI IPA SMA NEGERI 12 PEKANBARU - Relisia, Vezy; ', Herdini; ', Rasmiwetti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aimed to increase students achievement by implementation of learning method plane problem on learning topic of colloid in XI IPA SMA N 12 Pekanbaru. The type of this research is experimental research with randomized control group pretest-posttest design. Subject of this research are XI IPA 1 as the experimental class, XI IPA 3 as the control class which were determined randomly after conducting normality and homogeneity test. The experimental group was treated with the implementation of learning method plane problem while the control group without the implementation of learning method plane problem. The data analysis to test the hypothesis was using t-test right side. Based on the data analysis, it is obtaine tcount = 3,92 and ttable = 1,67 with ?=0,05, dk = 69, tcount > ttable is 3,92 > 1,67, It?s mean that the implementation of learning method plane problem can improve students achievement on the subject of colloid in XI IPA SMA Negeri 12 Pekanbaru. The influence of learning method plane problem to improvement of the student achievement as high as 18,21%.Keywords: Learning method plane problem, learning achievement, colloid